Comparison of oil and egg tempera paint systems using time-of-flight secondary ion mass spectrometry. (3rd July 2016) - Voras, Zachary E.; deGhetaldi, Kristin; Baade, Brian; Gordon, Eric; Gates, Glenn; Beebe, Thomas P.
Abstract : Time-of-flight secondary ion mass spectrometry (ToF-SIMS) is quickly becoming a critical tool in the field of art conservation. This technique provides high-resolution spatial maps of both inorganic and organic components located within cross-sectional samples collected from works of art. With recent advances in surface analysis, ToF-SIMS can now be used to identify specific amino acids present in protein-containing materials as well as fatty acids in drying oils. For example, the detection of the ion fragment associated with the amino acid hydroxyproline can be used to confirm the use of animal glue in a paint sample. As an analytical technique, ToF-SIMS avoids the need for derivatization/silylation reagents, with no interference by the presence of pigments. Furthermore, the layered systems that are often encountered in historical paint samples remain intact throughout the analytical procedure. This allows for the co-localization of organic and inorganic species in specific layers (e.g. egg yolk paint atop a glue ground). Because of this ability to localize the analytical signal to approximately 6 µm or less, the mass spectral information can be used to produce mass-resolved and spatially-resolve images which can be correlated to previous studies of the same samples. In this study, ToF-SIMS was used to analyze a paint cross section obtained from a painting attributed to Raphael, and another from a painting by the Sienese artist Matteo di Giovanni.